Objects of desire: values, choices and consumption in 14th-century Sassari (Studi di storia medioevale e di diplomatica - Nuova Serie, 2025)
Research in recent decades has highlighted the complexity of the relationship between objects and subjects in pre-capitalist societies. A relevant role plays written records, lists, and inventories. Inventories, an instrument of control and taking by those who prepare them, enter the sphere of material culture directly. They yield much information about the social life of objects, the circulation and levels of diffusion of consumer goods, and the similarities and differences between different social groups. However, the interaction between written documents and archaeological evidence makes it possible to approach the past more deeply. Using inventories and excavation data relating to objects that belonged to the Sassari community in the mid-fourteenth century, through the complementary nature of the data, this contribution explores the possibilities of recomposing the levels of consumption, the ideological and cultural aspects linked to the objects and the relationship of individuals with ‘things’ between signs of social distinction, economy, practical needs, and cultural practices.
Keywords: Goods; Inventories; Material Culture; Sassari; 14th Century